Wind Climate in Kongsfjorden, Svalbard, and Attribution of Leading Wind Driving Mechanisms through Turbulence-Resolving Simulations. (9th May 2012) - Esau, Igor; Repina, Irina
Abstract : This paper presents analysis of wind climate of the Kongsfjorden-Kongsvegen valley, Svalbard. The Kongsfjorden-Kongsvegen valley is relatively densely covered with meteorological observations, which facilitate joint statistical analysis of the turbulent surface layer structure and the structure of the higher atmospheric layers. Wind direction diagrams reveal strong wind channeled in the surface layer up to 300 m to 500 m. The probability analysis links strong wind channeling and cold temperature anomalies in the surface layer. To explain these links, previous studies suggested the katabatic wind flow mechanism as the leading driver responsible for the observed wind climatology. In this paper, idealized turbulence-resolving simulations are used to distinct between different wind driving mechanisms. The simulations were performed with the real surface topography at resolution of about 60 m. These simulations resolve the obstacle-induced turbulence and the turbulence in the non-stratified boundary layer core. The simulations suggest the leading roles of the thermal land-sea breeze circulation and the mechanical wind channeling in the modulation of the valley winds. The characteristic signatures of the developed down-slope gravity-accelerated flow, that is, the katabatic wind, were found to be of lesser significance under typical meteorological conditions in the valley.